1973
DOI: 10.1002/bip.1973.360120918
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation and orientation of DNA molecules

Abstract: synopsisA conductivity dispersion has been measured at very low frequencies (VLF) on several concentrated DNA solutions. By measuring simultaneously their electric birefringence decay, it is shown that the dielectric relaxation (which is related to the conductivity dispersion) is due to the molecular orientation. Different polarization mechanisms are discussed. It is concluded that the DNA polariaability measured in the VLF range can only be explained by the orientation of a permanent ionic dipole. It is sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

1974
1974
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…In studies of the relaxation of DNA in saline solutions, Takashima observed an a relaxation at around 100 Hz [1,16], for DNA molecular masses of 5 x 10^D . Hanss and Sakamoto [10,20,32,35,36,94] performed experiments on the same length molecules and found relaxations in the 5 to 1000 Hz range. Takashima used a capacitor with platinum-blacked electrodes to measure permittivity from 1 Hz to 1000 Hz.…”
Section: Simple Model Of Dipole Momentmentioning
confidence: 98%
See 2 more Smart Citations
“…In studies of the relaxation of DNA in saline solutions, Takashima observed an a relaxation at around 100 Hz [1,16], for DNA molecular masses of 5 x 10^D . Hanss and Sakamoto [10,20,32,35,36,94] performed experiments on the same length molecules and found relaxations in the 5 to 1000 Hz range. Takashima used a capacitor with platinum-blacked electrodes to measure permittivity from 1 Hz to 1000 Hz.…”
Section: Simple Model Of Dipole Momentmentioning
confidence: 98%
“…Higher-frequency measurements were made by a number of authors [40,[89][90][91][92]. Low-frequency measurements have been made by Takashima, Sakamoto, Hanss, and Tung [16,20,32,93]. In studies of the relaxation of DNA in saline solutions, Takashima observed an a relaxation at around 100 Hz [1,16], for DNA molecular masses of 5 x 10^D .…”
Section: Simple Model Of Dipole Momentmentioning
confidence: 99%
See 1 more Smart Citation
“…Oosawa (3) examined a similar fluctuation mechanism for rigid rods and concluded that attractive forces resulted if coupling occurred between counterion distributions along neighboring rods. It is the current beliefthat fluctuations in the small-ion distribution about a polyion are also responsible for the enhancement of the dielectric constant for linear polyelectrolytes at low frequencies of the external field (4)(5)(6)(7)(8)(9). It follows, therefore, that the dynamics of polyions would be greatly affected under conditions that promote large amplitude fluctuations in the small-ion distributions.…”
mentioning
confidence: 99%
“…Dapp = 1/2TK2, [5] where K = (4lTn/A)sin(0/2) is the scattering vector, n is the index of refraction, A = 488 nm, and 0 is the scattering angle. Fig.…”
mentioning
confidence: 99%